Analysis Of Consumer Preferences Related To Product Quality And Service Quality At Travel Resto X Yogyakarta - Puandira Caesha Naila Syaltha; Cita Eri Ayuningtyas; Marsudi Endang Sri Rejeki (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
The culinary business has been increasing year by year along with the growth of tourism in Indonesia. This is certainly very important to note considering that cuisine will always be one of the goals when people are traveling. Travel Resto X is one of the culinary services that offers dishes for tourists visiting Yogyakarta. However, the quality of products and services is often sidelined when visitor numbers are high. Therefore, there needs to be an evaluation for the management so that the business can compete with others. This study aims to understand consumer perceptions of product quality and service quality at Travel Resto X Yogyakarta. This type of research is quantitative descriptive with a survey approach. The subjects used in this study are consumers of tourists which is having lunch at Travel Resto X Yogyakarta during the study period. The sampling process used incidental sampling technique and involved 220 people. Data collection technique used questionnaire distribution. The questionnaire consisted of statements with 39 items using a likert scale and has tested for validity and reliability. The analysis technique was conducted using descriptive tests and categorization tables with the help of SPSS version 23.0. Based on the research data, it can be concluded that consumer perceptions of product quality at Travel Resto X Yogyakarta fall into the very good category with 10 respondents (4,5%), good category with 82 respondents (37,3%), not good category with 123 respondents (55,9%), and very poor category with 5 respondents (2,3%). Moreover, consumer perceptions of service quality at Travel Resto X Yogyakarta fall into the very good category with 10 respondents (4,5%), good category with 82 respondents (37,3%), not good category with 138 respondents (62,7%), and very poor category with 2 respondents (0,9%).